2003
DOI: 10.1007/s00267-002-2897-y
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer Environmental Monitoring and the Role of the Universities: The Case of Citizens' Environment Watch

Abstract: Universities can provide a stable home for launching collaborative community research projects. Citizens' Environment Watch (CEW), an environmental monitoring initiative based at the University of Toronto, has made significant contributions to environmental education and stewardship in Ontario, Canada. Following dramatic cuts in provincial monitoring programs, citizens and youth have used chemical parameters and biological indicators to gauge water and air quality, and to identify areas requiring remediation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 11 publications
2
69
0
1
Order By: Relevance
“…Kremen et al (2011) found that volunteers' confidence in identifying insects was higher when identifying to a more general taxon level than when asked to identify to species level. Additionally, volunteers increased their confidence over time, after training, or after repeated monitoring opportunities (Finn et al 2010;Savan et al 2003). These findings suggest that the low levels of confidence in performing citizen science tasks found in this study might not be completely different from confidence levels of existing volunteers, and that those confidence levels can increase over time.…”
Section: Discussionmentioning
confidence: 48%
“…Kremen et al (2011) found that volunteers' confidence in identifying insects was higher when identifying to a more general taxon level than when asked to identify to species level. Additionally, volunteers increased their confidence over time, after training, or after repeated monitoring opportunities (Finn et al 2010;Savan et al 2003). These findings suggest that the low levels of confidence in performing citizen science tasks found in this study might not be completely different from confidence levels of existing volunteers, and that those confidence levels can increase over time.…”
Section: Discussionmentioning
confidence: 48%
“…Still others secured funds to build a cabin for use by tourists and developed jewelry to sell to visitors. Other researchers reported increased social capital outcomes related to aspects of social capital such as increased size of personal networks (Overdevest et al 2004, Gooch 2005, Pollock and Whitelaw 2005, Jones et al 2006, Measham and Barnett 2008, Koss and Kingsley 2010, development of partnerships (Sharpe et al 2000, Savan et al 2003, and community influence (Pollock andWhitelaw 2005, Jones et al 2006).…”
Section: Increase In Social Capitalmentioning
confidence: 99%
“…CBR is "conducted by, for [,] or with the participation of community members" (Chopyak 2001, page 377). Examples emerging from the nascent literature on CBR report success in fostering a learning environment that leads to direct action and behavioral change in participating communities (Trumbell et al 2000, Robertson and McGee 2003, Savan et al 2003, Evans et al 2005. Road Watch was developed with an ultimate goal of linking researchers and citizens in a learning process that strengthens the information base and the number of individuals informed about wildlife movement across Highway 3.…”
Section: Evolution Into Community-based Researchmentioning
confidence: 99%